INKLYUZIV TA’LIM ISLOHATLARI VA ULARNING NAZARIY AHAMIYATI - Salohiddinova Sadoqat Sayriddin qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article talks about inclusive education, which is a relatively new concept for today. The article also discusses the importance of this concept for today, the work being done on the development of inclusive education in the republic, and the aspects that should be paid attention to in order for these works to produce effective results.